Forging a linguistic identity in the age of the Internet. (August 2014) - Danesi, Marcel
Today, computer-mediated communication (CMC) has made written communication a prevalent form of daily interaction through e-mails, Facebook, Twitter, text messages and the like. As a consequence, languages (written and spoken) seem to be shaped more and more by the modalities of digital media and of an 'instant communication response' culture. Linguistic identity, or the use of language to portray oneself as part of a community, is being shaped as well by the same modalities. Traditionally, the way individuals and communities used specific forms of language in face-to-face (F2F) situations shaped perceptions of identity (personal and communal). Now, the question can be asked: Are these changing in the age of the Internet, when CMC has extended the concept of community in a global way? This article will look at this question as it concerns linguistic identity in Italy, assessing its implications in the light of the traditional sociolinguistic study of language as a conveyor of identity.